Respostas termográficas em touros bubalinos submetidos à coleta de sêmen e avaliados sob condições agrometeorológicas no trópico úmido - BARROS, Daniel Vale (Universidade Federal do Pará, 2017)
Buffalo (Bubalus bubalis) livestock is mostly performed in the intertropical zone, where high temperatures prevail. Therefore the knowledge about buffaloes physiology on tropical environments and their possible responses due to tropical climate changes are essential. The objective of the study was to evaluate the variation in thermal comfort, physiological, hematological, seminal parameters and the superficial temperatures of buffalo bulls raised on humid tropical climate (Afi, Köppen classification). Ten buffaloes were kept in collective paddocks with free access to shade. During five months, data were registered from climatological meteorological station and three distinct dataloggers installed inside the stalls for calculating the Temperature and Humidity Index (THI). Respiratory rate (RR), heart rate (HR), rectal temperature (RT), superficial temperature of the eye (GLO), superficial temperature of the scrotum (ESC), superficial temperature of the right flank (FLd) and left flank (FLe) were registered. The Benezra´s Comfort Index (ICB) was also calculated. Semen collection was performed weekly by artificial vagina and blood sampling for assessment of blood counts were done monthly. The mean maximum of air temperature was 31.5°C and maximum a verage relative humidity was 93.2%. The THI was different only between periods (P<0.05). The RR, HR and ICB showed significant difference over the months and between shifts (P <0.05). RT differed between periods and reduced along months with lower value in August (37.8 ± 0.7°C). RT, GLO, FLd, FLe and ESC showed no diffe rence (P<0.05) for both periods and months. The hematocrit, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, gross motility and sperm vigor showed significant differences (P<0.05) along the months. The highest correlations between THI and superficial temperatures were between ITUmed and FLdmed (0.77; P<0.0001), ITUmed and FLemed (0.75; P<0.0001), ITUmed and GLO (0.72; P<0.0001), and ITUmed and ESC (0.41; P<0.0001). The highest correlation between internal temperature and surface temperature was TR and GLOmax (0.58; P<0.0001). Significant correlations were found between ICB and FR (0.97; P<0.0001), ICB and FC (0.89; P<0.0001), FC and FR (0.87; P<0.0001), THI and integrity of the plasma sperm membrane (-0.17; P<0.05). The results showed that animals had variations in thermal comfort and increased superficial temperature in the hottest periods of the day, however they were able to maintain homeothermy. Finally, the infrared thermography can be used as a noninvasive and auxiliary technique in studies about animal physiology and thermoregulation.